Ethyl 6-methyl-2-oxo-4-phenyl-1,2,3,4-tetrahydropyrimidine-5-carboxylate - S. Syed Nizar; C. A. M. A. Huq; A. Rasheeth; M. Nizam Mohideen (Acta Crystallographica Section E, 2008)
The title compound, C14H16N2O3, belongs to a group of esters of 2-oxo- and 1,2,3,4-tetrahydropyrimidine-5-carboxylic acids, which exhibit a wide spectrum of biological activities. The dihydropyrimidine ring adopts a screw-boat conformation. The crystal packing is stabilized by strong N—H...O and weak C—H...O intermolecular hydrogen bonds. An intramolecular C—H...O hydrogen bond is also present.